Effect of Signs Types on Level of Traffic Signs Understanding of Motorcyclists - Dewi Maulina; Maytika Dewi Ayu Shafira; Guritnaningsih P. Santoso (Psympathic: Jurnal Ilmiah Psikologi)
Insufficient comprehension of traffic signs among motorcyclists is a contributing factor to traffic accidents. Furthermore, the ability to comprehend these signs is closely tied to the cognitive process of accurately interpreting the information conveyed, with one of the key influencing factors being the representation of signs themselves.  Therefore, this research aimed to examine the effect of sign types on the understanding of traffic signs, utilizing an experimental research approach that employed a between-subject, randomized multi-group design. A sample of 80 motorcyclists aged 17-25 residing in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas was involved in the research. Participants were exposed to ten unfamiliar warning signs displayed on a computer, presented in three different formats, namely symbol, text, and symbol + text. Understanding of traffic signs was measured by level of signs comprehension (accuracy). The results showed that signs types significantly affected understanding of traffic signs. Furthermore, text and symbol + text signs resulted in higher level of understanding compared to symbols. The research implied the need for textual elements in the designs of warning signs to optimize understanding of traffic signs among motorcyclists.